Pengaruh Gaya Kepemimpinan, Motivasi kerja, dan Disiplin Kerja Terhadap Kinerja Karyawan Kantor Notaris Panam - Jeli Nata Liyas (Universitas PGRI Madiun, 2019)
This study aims to examine and analyze the influence of leadership style, motivation and discipline to employee performance Notary in Pekanbaru Tambusai lord street. Data collected through questionnaires and conducted on 71 employees who are in the way Notary Tambusai lord Pekanbaru. Analysis of the data in this study using SPSS version 16. In this study did not use sampling techniques since the sample studied is the whole of the population, or so-called census data and testing techniques used in this study include validity, reliability with Cronbach Alpha , classic assumption test and multiple linear regression analysis, to test and prove the hypothesis penelitian.Hasil analysis shows that the leadership style of significant positive effect on employee performance, motivation of no effect and no significant effect on employee performance and discipline significant positive effect on employee performance